Judicial Review Tap MPR RI terhadap Undang-Undang Dasar (UUD) 1945 Menurut Jimli Assdiddiqie - Amin, M. Sholihuddin (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article discusses about Jimli Asshiddiqie thinking about of MPR RI judicial review against the Constitution 1945. According to Jimli Asshiddiqie, eighth of Tap MPR/S is must be considered equivalent position with the law, because in our legal system was no longer recognized the existence of law products above the law, even though the form of law not the Consideration, but materially eighth of Tap MPR RI is Law. And when the Decree of MPR/S assessed has caused the loss of constitutional rights of certain parties, it can be requested testing (judicial review) in the Constitutional Court, as a constitutional test case stipulated in Law No. 24 of 2003 about Constitutional Court. In political jurisprudence perspective, authority of the Constitutional Court in resolving cases of judicial review Tap MPR against the Constitution 1945 as Jimli Asshiddiqie thought, has some similarities with the agency wilayah mazalim, the authorities is investigate and examine cases public beneficiaries are that cant be carried by hisbah officers. In a formal legal framework in Indonesia, wilayah mazalim can be equated to the Constitutional Court. Keywords: Judicial review, MPR, Jimli Asshiddiqie, political jurisprudence